Rainfall index insurance to help smallholder farmers manage drought risk - Díaz Nieto, J.; Cook, Simon E.; Läderach, Peter R.D.; Fisher, Myles J.; Jones, Peter G. (Informa UK Limited, 2010)
The struggle to find sustainable formal insurance for droughts in developing countries captures the attention of many in the development community for good reason. Droughts disrupt the development process, and the impacts of drought are exacerbated by an unwillingness on the part of the poor to invest combined with a lack of access to credit. This paper first examines the problems associated with traditional approaches to formal drought insurance and goes on to examine the potential of index insurance that is event-driven. A combined weather-generation and crop simulation modelling approach is used to estimate site-specific risks. The method is demonstrated in a case study for dry bean production in Honduras.